1283 MEDICATION-RELATED HARM (MRH) IN OLDER PEOPLE AFTER LEAVING HOSPITAL - AN UNDER-REPORTED EGYPTIAN CHALLENGE. (16th January 2023) - Jamil, M; Sweed, H; Abou-Hashem, R; Hamed, H; Ali, K
Abstract: Introduction: Ageing is associated with multimorbidity, polypharmacy and medication-related harm (MRH). A 2013 systematic review reported only one study of medication errors (MEs) in older Egyptian patients. Our study investigated MRH (adverse drug reactions (ADR), drug errors, and non-adherence) in older Egyptian adults after hospital-discharge. Methods: Between 2018 and 2020, we recruited 400 Egyptian patients, aged ≥60 years on discharge from Geriatrics and Internal Medicine wards from 3 hospitals, and followed them up for 8 weeks. Study procedures adopted a modified PRIME trial methodology (1). Results: The average age of study participants was 71 (range 60 to 93, SD +/- 6.29) years with 53% females. In the cohort of 325 patients completing follow up, MRH occurred in 99 patients (incidence of 30.5%), with 5 patients (5.1%) experiencing a fatal MRH. Almost two thirds (65.7%) of MRH events were secondary to ADRs, 2 % related to non-adherence, 18.2 % due to both ADR and non-adherence, and 14% related to MEs. Multivariate logistic regression analysis showed that non-adherence (p-value 0.000, OR- 95% CI: 36.029), inappropriate prescription using Beer's criteria (p 0.000, OR- 95% CI: 6.589), length of stay >7days (p 0.001, OR- 95% CI: 6.176), presence of Ischaemic Heart Disease (IHD) (p 0.000, OR- 95% CI: 5.695), Platelets count ≤ 245X 109/L (p 0.021, OR- 95% CI: 2.640), and dementia medications (p 0.017, OR- 95% CI: 4.616) were all significantly associated with MRH. Conclusions: Medication-related harm in older Egyptian adults is common after hospital discharge. An integrated care pathway is required targeting high-risk older patients. Reference: 1. Stevenson J, Parekh N, Ali K et al. Protocol for a Prospective (P) study to develop a model to stratify the risk (RI) of medication (M) related harm in hospitalized elderly (E) patients in the UK (The PRIME study). BMC Geriatrics 2016; 16: 22. https://doi.org/10.1186/s12877-016-0191-8 .